FITTING THE SPECTRA OF PIONS, KAONS, PROTONS, AND ANTIPROTONS IN RELATIVISTIC CU + CU COLLISIONS (Euro-Asia Conferences, 2021)
There are two main problems in quantum chromodynamics (QCD) related to the vacuum structure that can only be solved by relativistic nuclear physics. These problems are: color charge configuration and spontaneous disruption of chiral symmetry. The confinement means that there are no colored objects in the observed spectrum of hadron states. From the point of view of quarks-gluons' assumptions about the structure of hadrons, the confinement means that quarks and gluons cannot propagate at distances greater than 1fm (hadron size) [1]. However, this assertion is valid only at normal nuclear densities